2007
DOI: 10.1002/app.26707
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrochemical properties of polyamide and polyaniline

Abstract: Electrochemical properties of well-defined molecular structured polyamide with amine-capped aniline pentamer in the main chain and conventional polyaniline were investigated and discussed. CV results suggest that the synthesized polyamide shows a relatively complicated redox process than conventional polyaniline during potential cycling. Differences in ESI characterization revealed that the synthesized polyamide exhibits higher electronic conductivity and lower resistance than the conventional polyaniline. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…However, because graphene has a pronounced tendency to agglomerate in a polymer matrix, pristine graphene is unsuitable for intercalation by large species and does not form homogeneous composites. PANI is most likely chosen to be the conductive polymer backbone for RGO‐polymer composites because of its ease of synthesis, excellent environmental stability, and many interesting chemical, electrical, and optical properties and also for its tremendous applicability in electronic, optical, and magnetic materials such as information storage, rechargeable batteries, electro chromic display devices, sensors, nonlinear optics, composites, field emission (FE) displays, etc 13–16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because graphene has a pronounced tendency to agglomerate in a polymer matrix, pristine graphene is unsuitable for intercalation by large species and does not form homogeneous composites. PANI is most likely chosen to be the conductive polymer backbone for RGO‐polymer composites because of its ease of synthesis, excellent environmental stability, and many interesting chemical, electrical, and optical properties and also for its tremendous applicability in electronic, optical, and magnetic materials such as information storage, rechargeable batteries, electro chromic display devices, sensors, nonlinear optics, composites, field emission (FE) displays, etc 13–16…”
Section: Introductionmentioning
confidence: 99%
“…PANI is most likely chosen to be the conductive polymer backbone for RGOpolymer composites because of its ease of synthesis, excellent environmental stability, and many interesting chemical, electrical, and optical properties and also for its tremendous applicability in electronic, optical, and magnetic materials such as information storage, rechargeable batteries, electro chromic display devices, sensors, nonlinear optics, composites, field emission (FE) displays, etc. [13][14][15][16] Covalent attachment is the only tool that allows us to prepare a composite with efficient filler/polymer interactions leading to composites with improved properties. In this article, we describe a series of experiments carried out to incorporate a conductive network into polyvinyl chloride (PVC) and to obtain composites with good electrical properties and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Various PANI nanostructures display the improved optical, structural, electronic and electrical properties which might act as useful candidate for the application in electrochemical, electrochromic, biosensors and chemical sensors devices. [63][64] Recently, PANI nanomaterials have gained a great attention in the field of sensors including gas sensor, biosensor and chemical sensors. 65 70 The fabricated phenol sensor based on layered PANI nanosheets exhibited a high sensitivity of ~1485.3 µA.mM -1 .cm -2 and very low detection limit of ~4.43 µM with correlation coefficient (R) of ~0.9981 and short response time (10 s).…”
Section: The Efficient Electrode Of Layered Polyaniline (Pani) Nanoshmentioning
confidence: 99%
“…Moreover, it has been reported that the properties of PANI could be easily improved by acid dopants and the blending with organic/inorganic semiconducting nanomaterials 98 . Recently, the composites of PANI and Gr exhibit tremendous applicability in many electronic, optical, electrochemical and biosensors 99 .The PANI/Gr composites display significant electrical conductivity and electrochemical properties toward various electrochemical, electrochromic and bionsensing devices. 100 The surface of Gr thin film ( Fig.…”
Section: Semiconducting Nano Composites For Chemosensors Modified Elementioning
confidence: 99%
“…Among conducting polymers, the class of compounds which recently has been widely investigated for sensing applications is PANI because of its inexpense, easy availability of raw materials for its synthesis, ease of processing, high conductivity, and simple doping process [101] . Despite its extensive application in electrochemical biosensing, mostly as an enzyme or antibody immobilization matrix [86] , the performance of conventional PANI fi lms is strongly thickness dependent: the higher the thickness, the poorer the diffusion of analytes towards the sensing element and consequently the sensitivity of measurements decreases [102] .…”
Section: Conductive Polymer Nanostructures Used In Catalytic Biosensorsmentioning
confidence: 99%